2016
DOI: 10.1097/md.0000000000005488
|View full text |Cite
|
Sign up to set email alerts
|

A lower dosage of imatinib in patients with gastrointestinal stromal tumors with toxicity of the treatment

Abstract: This study investigated the efficiency and safety of imatinib in the lower dose (300 mg/d) in patients with gastrointestinal stromal tumor (GIST) who cannot tolerate imatinib in the standard dose (400 mg/d).Steady-state imatinib trough concentration (Cmin) values in 18 patients with GIST who were taking 300 mg/d or 400 mg/d imatinib were measured. The clinical features, toxicity data, and follow-up data were collected.Around 18 patients with GIST were investigated in which 9 patients received 300 mg/d imatinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…If possible, it is recommended to monitor the imatinib plasma concentration on the following patients: patients who developed progression under first-line imatinib therapy at 400 mg/d dose; patients with severe drug adverse reactions which are caused by excessive imatinib plasma concentration. It is reasonable to reduce imatinib dose with minimal effective blood concentration; for incompliant patients who did not take regular medication, if the plasma imatinib concentration is lower than 1,100 ng/mL, the clinical efficacy will decrease and the disease will progress rapidly ( 59 , 60 ).…”
Section: Principles Of Molecular Targeted Drug Therapymentioning
confidence: 99%
“…If possible, it is recommended to monitor the imatinib plasma concentration on the following patients: patients who developed progression under first-line imatinib therapy at 400 mg/d dose; patients with severe drug adverse reactions which are caused by excessive imatinib plasma concentration. It is reasonable to reduce imatinib dose with minimal effective blood concentration; for incompliant patients who did not take regular medication, if the plasma imatinib concentration is lower than 1,100 ng/mL, the clinical efficacy will decrease and the disease will progress rapidly ( 59 , 60 ).…”
Section: Principles Of Molecular Targeted Drug Therapymentioning
confidence: 99%
“…They found that imatinib plasma C min at 300 mg/day was 1559 ± 478 ng/mL, which was comparable to that in patients who were treated with 400 mg/day (C min 2262 ± 1009 ng/mL). [24] In this case, long-term follow-up showed no signs of tumor recurrence. Although the C min value of 1015.7 ng/mL was slightly below the threshold range given above, it might indicate that the imatinib plasma concentration was effective.…”
Section: Discussionmentioning
confidence: 73%